Plasma metabolite profiles in children with current asthma. Issue 10 (3rd July 2018) - Kelly, R. S.; Sordillo, J. E.; Lasky‐Su, J.; Dahlin, A.; Perng, W.; Rifas‐Shiman, S. L.; Weiss, S. T.; Gold, D. R.; Litonjua, A. A.; Hivert, M.‐F.; Oken, E.; Wu, A. C.
Summary: Background: Identifying metabolomic profiles of children with asthma has the potential to increase understanding of asthma pathophysiology. Objective: To identify differences in plasma metabolites between children with and without current asthma at mid‐childhood. Methods: We used untargeted mass spectrometry to measure plasma metabolites in 237 children (46 current asthma cases and 191 controls) in Project Viva, a birth cohort from eastern Massachusetts, USA. Current asthma was assessed at mid‐childhood (mean age 8.0 years). The ability of a broad spectrum metabolic profile to distinguish between cases and controls was assessed using partial least squares discriminant analysis. We used logistic regression models to identify individual metabolites that were differentially abundant by case–control status. We tested significant metabolites for replication in 411 children from the VDAART clinical trial. Results: There was no evidence of a systematic difference in the metabolome of children reporting current asthma vs. healthy controls according to partial least squares discriminant analysis. However, several metabolites were associated with odds of current asthma at a nominally significant threshold ( P < .05), including a metabolite of nicotinamide (N1‐Methyl‐2‐pyridone‐5‐carboxamide (Odds Ratio (OR) = 2.8 (95% CI 1.1‐8.0)), a pyrimidine metabolite (5, 6‐dihydrothymine (OR = 0.4 (95% CI 0.2‐0.9)), bile constituents (biliverdin (OR = 0.4 (95%CI 0.1‐0.9), taurocholate (OR = 2.0 (95% CI 1.2‐3.4)), two peptides likely derived from fibrinopeptide A (ORs from 1.6 to 1.7), and a gut microbiome metabolite (p‐cresol sulphate OR = 0.5 (95% CI 0.2‐0.9)). The associations for N1‐Methyl‐2‐pyridone‐5‐carboxamide and p‐cresol sulphate replicated in the independent VDAART population (one‐sided P values = .03‐.04). Conclusions and Clinical Relevance: Current asthma is nominally associated with altered levels of several metabolites, including metabolites in the nicotinamide pathway, and a bacterial metabolite derived from the gut microbiome.